SOCIAL JUSTICE AND HUMAN EDUCATION IN PHILOSOPHICAL VIEWS OF RUDAKI (Scientific journal of the Fergana State University, 2026)
The article examines the issue of social justice and human education in the views of Abu Abdullah Jafar Rudaki, Rudaki explains that human education is of particular importance in restoring social justice. Rudaki reveals such qualities as love, humanity, kindness and generosity, people's responsibility for their actions. Rudaki's poems sometimes criticize violence, poverty, and social inequality. He called for compassion for the poor and emphasized the importance of rational and fair governance.